Forecasting the Export Value of Oil and Gas in Indonesia using Autoregressive Integrated Moving Average (ARIMA) - Ansari Saleh Ahmar; Abdul Rahman; Parkhimenko Vladimir Anatolievich; Rusli Rusli; Sitti Masyitah Meliyana R. (Quantitative Economics and Management Studies, 2023)
This study aims to utilize the ARIMA method to predict the value of Indonesia's oil and gas exports. As quantitative research, it employs secondary data sourced from the Central Bureau of Statistics of the Republic of Indonesia's website. The data spans January 2010 to March 2022 and are presented on a monthly basis. Through the results and discussion, three ARIMA models were established, namely ARIMA (1,1,0), ARIMA (0,1,1), and ARIMA (1,1,1). Among these models, the ARIMA (0,1,1) model with an AIC value of 2047.65 was found to be the most suitable for forecasting Indonesia's oil and gas exports. The forecasted values for the next five periods were 1254.124 (April 2022), 1309.678 (May 2022), 1289.236 (June 2022), 1296.758 (July 2022), and 1293.990 (August 2022).